Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

If [tex]\( a \cdot t = c \cdot g \)[/tex], then [tex]\( \frac{a}{g} = \)[/tex] ?

Sagot :

To solve for [tex]\(\frac{a}{g}\)[/tex] given [tex]\(a \cdot t = c \cdot g\)[/tex], let's follow these steps:

1. Start with the given equation:
[tex]\[ a \cdot t = c \cdot g \][/tex]

2. To isolate [tex]\(\frac{a}{g}\)[/tex], we need to rearrange the equation. First, divide both sides of the equation by [tex]\(g \cdot t\)[/tex]:
[tex]\[ \frac{a \cdot t}{g \cdot t} = \frac{c \cdot g}{g \cdot t} \][/tex]

3. Simplify both sides of the equation:
[tex]\[ \frac{a}{g} = \frac{c}{t} \][/tex]

Therefore, the solution is:
[tex]\[ \frac{a}{g} = \frac{c}{t} \][/tex]